Near Full-Length Genomic Characterization of Two Novel HIV-1 Unique Recombinant Forms (CRF01_AE/CRF07_BC) Among Men Who Have Sex with Men in Shijiazhuang City, Hebei Province, China - Han, Leilei; Li, Hanping; Wang, Lijing; Jia, Lei; Han, Jingwan; Li, Tianyi; Wang, Xiaolin; Liu, Yongjian; Li, Jingyun; Lu, Jianhua; Qu, Xiaojing; He, Xuhui; et al. (AIDS research and human retroviruses, 2021)
Unique recombinant forms (URFs) are more likely developed among HIV-1 infections through men who have sex with men (MSM) because of cocirculation of multiple subtypes. In this study, two novel URFs deriving from two HIV-positive subjects (HB010014, HB010063) were identified in Shijiazhuang, Hebei province, China, and two sequences formed a distinct monophyletic cluster. Further recombination analysis showed that of two new URFs were consisted of circulating recombinant form (CRF)01_AE and CRF07_BC. The subregion phylogenetic analysis indicated that CRF01_AE segments were traced back to cluster 4 of CRF01_AE strains, which were prevalent among HIV-1 infections through MSM in China. New URFs being developing gradually and spreading released that more and more novel recombinant strains of HIV-1 could be developed, which means that the past prevention strategies need to be adjusted.